Healthcare-associated fungal infections and emerging pathogens during the COVID-19 pandemic - Shah, Krish; Deshpande, Mukund; Shah, P. (Frontiers in Fungal Biology, 2024)
Over 150 million people have severe fungal infections, which leads to approximately more than one million deaths per year. Moreover, diseases like cancer, which involve long-term therapy and prophylactic use of antifungal drugs, have increased the emergence of drug-resistant fungi, which include highly virulent strains such as Candida auris. The clinical spectrum of fungal diseases ranges from superficial mucocutaneous lesions to more severe and life-threatening infections. This mini-review discusses the effects of hospital environments, especially during the COVID-19 pandemic, on fungal infections and emerging pathogens. The review also provides insight into various antifungal drugs and their existing associated challenges, thereby driving the need to search for novel antifungal agents.